Pharmacogenomics predictors of aromatic antiepileptic drugs-induced SCARs in the Iraqi patients - Ali Fadhel Ahmed; Dzul Azri Mohamed Noor; Majeed Arsheed Sabbah; Nur Fadhlina Musa; Nur Aizati Athirah Daud (Heliyon)
Introduction: Severe cutaneous adverse reactions (SCARs) are life-threatening and often linked to antiepileptic drugs (AEDs). Common types of SCARs include Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug reaction with eosinophilia and systemic symptoms (DRESS). Immune-mediated mechanisms involving human leukocyte antigen (HLA) alleles have been implicated in the pathogenesis of this reaction. This study examines the association between specific HLA alleles (HLA-A, -B, and -DRB1) and AED-induced SCARs in the Iraqi population. Methodology: A total of 50 patients diagnosed with SCARs and 90 tolerant controls were recruited from Dr. Saad Al-Wattari Hospital for Neurological Sciences and Baghdad Hospital - Medical City. HLA genotyping was performed using PCR-SSO method from peripheral blood samples. Statistical comparisons were made using the t-test or chi-square test, while univariate logistic regression with Bonferroni's correction (p < 0.05) were used to assess associations between HLA alleles and SCARs. Results: Among the patients, SJS was the most prevalent type of SCARs observed. Analysis of HLA allele frequencies revealed significant associations between specific alleles. HLA-A∗02:01 was found to be significantly associated with a lower risk of AED-induced SJS (OR = 0.36; 95 % CI: 0.13–0.97), while HLA-A∗24:02 and HLA-B∗15:02 were associated with an increased risk of AED-induced SJS (OR = 3.60; 95 % CI: 1.21–10.72 and OR = 4.41; 95 % CI: 1.18–16.47, respectively). For AED-induced TEN, HLA-A∗01:02, HLA-B∗15:02, and HLA-B∗52:01 showed significant associations (OR = 6.92; 95 % CI: 1.39–34.37 and OR = 6.55; 95 % CI: 1.62–26.52, respectively), with HLA-DRB1∗03:01 being highly significant (OR = 5.09; 95 % CI: 1.72–15.00). Additionally, HLA-B∗40:02 was strongly associated with AED-induced DRESS (OR = 29.33; 95 % CI: 3.50–245.32). Conclusion: This study identifies key HLA alleles associated with AED-induced SCARs in the Iraqi population. These findings could facilitate personalized medicine approaches, aiding in better prediction and prevention of SCARs in AED therapy.